Antibacterial activity of Copaifera reticulata “Copaiba” on Porphyromonas gingivalis isolated from patients with periodontitis - Ramos Perfecto, Donald (2014)
Objective: the objective of this study was to evaluate the antibacterial activity of oleoresin Copaifera reticulate (C. reticulata) on Periodontopathogenic bacteria Porphyromonas gingivalis (P. gingivalis ) Methodology: From a total of 43 samples of subgingival plaques of patients with periodontitis, it was isolated 20 clinical strains of P. gingivalis, the preliminary identification occurred by growth of black pigmented colonies on blood agar with hemin and vitamin K, these colonies were purified to test for catalase, oxidase and TSI, Citrate, Urea, Sim means. Definitive identification was held by means of the automated testing of Api 20 A. Once the strain were isolated the diffusion test was performed on plate, with discs loaded with the oleoresin at concentrations of 100 %, 50 %, 25 %, 12,5 %, 6,25 %, 3,12 %, 1,56 %, 0.78%, 0,39 %, 0,19 %, taking 0,12 % chlorhexidine as a positive control, and copaiba dimethylsulfoxide (DMSO) as a negative control. Results: The Initial-media sensitivity was determined at 100% copaiba for P. gingivalis, being the average minimum inhibitory concentration at 3.43%. The differences between other concentrations of Copaifera reticulata and positive control were statistically significant for Kruskal Wallis test (P < 5 %). Conclusion: Based on experimentation, we conclude that the Copaifera reticulata has antibacterial activity on P. gingivalis, being the major activity at 100% concentration, beating the 0,12 % chlorhexidine, product widely used as a complement of periodontitis tratment. Proposing a possible use of copaiba oleoresin in this pathology.